The first five minutes how to make a great first impression in any business situation - Mitchell, Mary 1949- (John Wiley, 1998)
Business communications expert Mary Mitchell gives business people and job seekers everything they need to make the right first impression, whether in person--at job interviews, sales calls, or social gatherings--or via letter, fax, or e-mail. Based on Mitchell's popular corporate seminars which have been attended by employees of Arthur Young, Ritz Carlton Hotels, Merck, and other top firms, The First Five Minutes.